Women Movements’ Perspective in E.L. James’s Fifty Shade of Trilogy - Arum Puspita, Gusti Ketut Mia (International Journal of English Literature and Social Sciences (IJELS), 2019)
Abstract: Feminism is a popular terms dealing with inequality, gender, sex, education, cultural, unfair, legal, law, economy, empowerment of female against male. The women movements are the action for women to be able to speak for themselves. Many women write literatures to express their thought of feminism to inform and educate readers about the inequality. Then, the focus of this research is to find out the women movements’ perspectives on Fifty Shades Trilogy to make reader realize the substantial matters about the author’ hidden message. This research is using interpretivist Paradigm that is aimed to understand the subjectivity world of human experiences. The approach is qualitative methodology and using the novels as the primary data. Regarding to the National Women’s Liberation Conference in 1978 there were seven demands was finialized. The seven demands are 1) equal pay for equal work, 2) equal education and equal opportunities, 3) free contraception and abortion on demand, 4) free 24-hour nurseries, 5) legal and financial independence for women, 6) an end to discrimination against lesbians, 7) freedom for all women from intimidation by the threat or use of male violence; and end to the laws, assumptions and institutions which perpetuate male dominance and men’s aggression towards women. The symbolic interactionism theory by Herbert Blumer collides the meaning, thinking and language from conversation on the story and found the seventh demands that written on the novel.